STRESS AND SELF EFFICACY AMONG NURSES IN NEONATAL INTENSIVE CARE UNITS - Elkazaz, Rehab Hani; Berma, Abeer Elsayed (International Journal of Research -GRANTHAALAYAH, 2017)
Stress is one of the main factors affecting one's efficiency as well as staff health and quality of nursing services. Neonatal units can be stressful environments for nurses, infants and families as well. Since there is no evidence in this regard in Egypt. Aim of the study: to determine the relationship between stress and self-efficacy among staff nurses in neonatal intensive care units (NICU) in Port Said. Method: This was a descriptive correlation study including thirty three nurses working in NICUs of hospitals in Port Said. The data collection tools were a self-efficacy and stress scales. Results: It reveals that, there were statistically significant correlations between staff nurses self-efficacy and their stress toward financial environment. Also there were negative correlation between stress psychological domain, physical environment and services, work relationship with nurses as well as physicians and self-efficacy assessment. Also reveals that, there were no statistical significant relations between workplace stressors, staff nurses self-efficacy and their socio-demographic characteristics. But there are statistically significant relation was found between staff nurses self-efficacy and their duration of nursing experience. The findings of the present study show that increasing stress in the aspects of psychological, physical environment and services domain, in addition to, social environment with nurses and physicians among nurses would lead to decrease self-efficacy. Also the present study reveals that there were statistically significant correlations between staff nurses self-efficacy and their stress toward financial environment. So, staff nurses should attend continuing educational programs on staff nurses' quality outcomes such as enhancing staff nurses' self-efficacy and strategies coping to reduce stress.